An Overview of Eqrem Cabej’s Literary Thought - Dhima, Edlira (Richtmann Publishing, 2012)
For over half a century, Cabej, like a few others, saw great achievements for his contribution to various fields of Albanologyand Balkanology. The breadth of his interests and his scientific productivity are perspicuous testimonies of the fact that he was a giftedscientist of European caliber, who dedicated his entire life to science. The writings of great linguists and humanists such as EqeremCabej are part of those elements, which constitute the cultural foundations of a nation. Just like the mighty mountains, such contributionscast their shade and rest their weight everywhere. Even when lacking the possibility or the need to analyze them in detail, the widemasses of the common people can feel their irradiating influence, and most of all, they truly believe them. Eqerem Cabej is a profoundscholar of the genesis of Albanian literature. He created the theoretical core of Albanian Romanticism and started the theoretical initiativeof the Modern Albanian Literature. As a pioneering theorist of the latter, which inevitably includes language too, he put forth prodigiousefforts to make it as rich and dynamic as possible, and as developed, and particularly, as aesthetic as it could be. His work, just like thebusy hum of the working bee, was persistent and tireless — the work of a great master. His work will be traveling the Albanian-speakingworld in perpetuity, due to its being as language-forming as it is world-forming.